2003
DOI: 10.1086/368172
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 Genome and Antigen in Acute Multiple Sclerosis Lesions

Abstract: Evidence for a candidate multiple sclerosis (MS) virus, human herpesvirus 6 (HHV-6), was sought in biopsy specimens of acute lesions that presented clinically as cerebral tumors obtained from 5 patients. Histopathology, magnetic resonance imaging, and clinical course confirmed the diagnosis of MS in each case. A sensitive in situ polymerase chain reaction (ISPCR) method was used to detect HHV-6 genome, in conjunction with immunocytochemical staining (ICC) to detect viral and cellular antigens. ISPCR revealed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 54 publications
8
78
0
2
Order By: Relevance
“…HHV-6 has also been detected, albeit at low levels, in Hodgkin's lymphoma and angioimmunoblastic lymphadenopathy, 42 and has been implicated in multiple sclerosis. 43 HHV-6 infection is common in early childhood, when it presents as a febrile illness with rash, known as roseola. In healthy adults, HHV-6 DNA has been detected in saliva and salivary gland epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 has also been detected, albeit at low levels, in Hodgkin's lymphoma and angioimmunoblastic lymphadenopathy, 42 and has been implicated in multiple sclerosis. 43 HHV-6 infection is common in early childhood, when it presents as a febrile illness with rash, known as roseola. In healthy adults, HHV-6 DNA has been detected in saliva and salivary gland epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In disease in which HHV-6A has been implicated (34), this viral variant could reach the CNS via infected inflammatory cells. The hallmark of the MS lesion is inflammation in which both oligodendrocytes (17) and astrocytes have been shown to contain HHV-6 (7,27). Direct viral infection of these cells may be associated with abundant expression of viral antigens and might contribute to an immune-mediated response against viral antigens or shared sequence or conformational homology with self-proteins (molecular mimicry).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on autopsy brain samples from patients with MS have reported a higher frequency of HHV-6 DNA in MS plaques as opposed to normal-appearing white matter of the same patients and to unaffected brain specimens (7,17), and a recent investigation has documented significantly higher levels of HHV-6 gene transcripts in both lesional and normal-appearing white matter in autopsy brain samples from MS patients than in those from normal controls (27).…”
mentioning
confidence: 99%
“…Typically, CNS infections by HHV-6 lead to benign viral latency, a strategy for persistence used by all members of the herpesvirus family. HHV-6 has been recently demonstrated to infect primary human oligodendrocytes in vitro and in vivo (Albright et al, 1998;Mock et al, 1999;Blumberg et al, 2000;Goodman et al, 2003), as well as human astrocytes (He et al, 1996;Donati et al, 2003), but virtually nothing is known about its effects on glial precursor cells, from which both oligodendrocytes and astrocytes originate.…”
Section: Introductionmentioning
confidence: 99%